2017
DOI: 10.1002/pat.4021
|View full text |Cite
|
Sign up to set email alerts
|

Tensile modulus of polymer/CNT nanocomposites by effective volume fraction of nanoparticles as a function of CNT properties in the network

Abstract: In this article, the effects of filler network and interphase between polymer matrix and nanoparticles on the tensile modulus of polymer/carbon nanotubes (CNT) nanocomposites are assumed by the effective volume fraction of nanoparticles. By this approach, the Takayanagi model is developed for polymer/CNT nanocomposites above percolation threshold. Also, the effective factors for filler network including the number (N), aspect ratio (α) and percolation threshold (ϕp) of CNT are correlated to three main paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The expected reason for this drop‐off is the presence of agglomerates at higher loading of nanotubes filler because of their more selectivity with one phase they form clusters as can be seen in SEM images of PU/PS‐NO 2 /FMWCNTs 0.1 g. The second reason might be the non‐homogeneity or non‐homogeneous dispersion of filler in both polymer phases. The agglomerates can cause globules and initiate crack propagation and these cracks reduce the modulus and tensile strength of the material 32 . Results indicate that uniform dispersion and filler alignment plays vital roles in mechanical determination.…”
Section: Resultsmentioning
confidence: 99%
“…The expected reason for this drop‐off is the presence of agglomerates at higher loading of nanotubes filler because of their more selectivity with one phase they form clusters as can be seen in SEM images of PU/PS‐NO 2 /FMWCNTs 0.1 g. The second reason might be the non‐homogeneity or non‐homogeneous dispersion of filler in both polymer phases. The agglomerates can cause globules and initiate crack propagation and these cracks reduce the modulus and tensile strength of the material 32 . Results indicate that uniform dispersion and filler alignment plays vital roles in mechanical determination.…”
Section: Resultsmentioning
confidence: 99%
“…However, to integrate the specific functional properties in aluminium matrix composites, proper selection of the reinforcements is of prime importance, as their ductility has often seen to be compromised with the incorporation and increase in ceramic particle concentration [5][6]. Since the last few years multiwall carbon nanotubes (MWCNs) have led to a new era in material research, because of their high aspect ratio, impressive thermo-oxidative stability, low thermal expansion coefficient, good electrical conductivity, along with superlative mechanical properties, like high modulus of elasticity, high tensile strength and high bending strength [7][8][9]. In this regard, multiwall carbon nanotubes reinforced metal matrix composites has proven to generate admirable combination of physical, mechanical, thermal and electrical properties [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the friction and wear modification of polyimide (PI) composites had been achieved by introducing multiscale CFs, the main mechanism is the decrease in stress concentration between the matrix and reinforcement phase caused by multiscale characteristics of fillers [12]. CNTs with high elastic modulus and strength are also usually used as additives to enhance the tribological and mechanical characters of polymers matrix composites, and the lubrication and wear mechanism is similar to SCFs reinforced composites [13][14][15].…”
Section: Introductionmentioning
confidence: 99%